THE ROLE OF TEACHING ENGLISH TO YOUNG LEARNERS WORLDWIDE - Bobokeldieva Maftuna Abdusamad qizi (Journals Park Publishing, 2025)
As English continues to dominate as the global language of communication, early English education has gained increasing importance. Teaching English to young learners (TEYL) is no longer a luxury but a strategic decision in education systems around the world. This article explores why early language acquisition matters, how children respond to English at different ages, and what global practices are emerging in this field. It analyzes theoretical perspectives, teaching methods, and implementation challenges to offer a well-rounded view of TEYL in today’s multilingual and multicultural societies.
Keywords: Young learners, English as a Foreign Language (EFL), early childhood education, second language acquisition, global education, language pedagogy.